INTERCONNECTION OF THE TAJIK AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2026)
Languages of the world possess their own unique linguistic significance. In society, a language that holds a higher status and position compared to others naturally exerts a profound influence on them. This article examines the interrelation between the Tajik and Uzbek languages, the influence of the Tajik language on Uzbek, and the reasons for this process at the phonetic and morphological levels.